Enhancing Performance and Stability of Wing-Alone UAV: A Comprehensive Mathematical Model and Simulation Approach Using MATLAB and Simulink - G. Ramanan; N. Rahul; V. E. Sathishkumar; Indraraj Upadhyaya (Modelling and Simulation in Engineering)
This study is aimed at developing a comprehensive mathematical model and simulation using MATLAB and Simulink for both a civil transport aircraft and a wing-alone UAV. The novel objective of this study is enhancing the performance and stability aspects of the wing-alone UAV through code-based reports and the implementation of custom MATLAB algorithms. The wing-alone UAV demonstrated a 15% improvement in aerodynamic efficiency and a 10% reduction in overall weight compared to baseline designs. Longitudinal stability was enhanced by optimizing the slope of the pitching moment curve (Cmα) to achieve a neutral point at a center of gravity (CG) location of 0.4, ensuring stability for varying mission profiles. The model also achieved a 20% reduction in trim lift coefficient for cruise conditions. Using the flat Earth equations and MATLAB’s ode15s solver, the UAV’s 12 states, including translational and rotational motions, were accurately simulated, and validated by integrating Euler and Poisson’s kinematical equations for computing geodetic positions and body frame orientations. The UAV’s weight components, including battery, propulsion, and structural weights, were analyzed, demonstrating a 12% reduction in power requirements during climb at optimal angles of attack. Performance analyses revealed a maximum rate of climb at 3.5 m/s and optimal aerodynamic efficiency for minimum drag at a cruise velocity of 25 m/s. The customized MATLAB algorithm enabled closed-loop control system designs for the elevator, achieving less than 10% overshoot and a settling time of under 10 s. These quantitative insights contribute to advancing wing-alone UAV stability and performance, making this research applicable to both civil and military applications.